2009
DOI: 10.1515/znb-2009-11-1206
|View full text |Cite
|
Sign up to set email alerts
|

,, ... und ehrt mir ihre Kunst!“ – Evaluierung historischer und neuer Synthesewege zu 1,5-Dihydroxy-6-oxo-1,6-dihydropyridin-2-carbonsäure und 1,3-Dihydroxy-2-oxo-3-pyrrolin-4-carbonsäure / “. . . and honour their art!” – Evaluation of Historical and New Routes to 1,5-Dihydroxy-6-oxo-1,6- dihydropyridine-2-carboxylic Acid and 1,3-Dihydroxy-2-oxo-3-pyrroline-4-carboxylic Acid

Abstract: Gewidmet Professor Hubert Schmidbaur anlässlich seines 75. GeburtstagsThe historical and recent literature describing synthetical pathways to the title compounds is comprehensively summarized and evaluated. Routes via 2,5-dioxoadipic acid or 2,5-dihydroxymuconic acid as intermediates could not be followed reproducibly. 3-Hydroxy-2-oxo-2H-pyran-6-carboxylic acid and ethyl 3-hydroxy-2-oxo-3-pyrroline-4-carboxylate were fully characterized by spectroscopic methods and single-crystal X-ray diffraction. Both compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A search of the Cambridge Structural Database (CSD Version 5.42, update of November 2020; Groom et al, 2016) for the 3hydroxy-1,5-dihydro-pyrrol-2-one fragment revealed 79 hits. Only 27 of these hits contain a fragment with the same structure as that of the title compound [refcodes: BOQXEN (del Corte et al, 2019), CIKPAQ (Sarkar et al, 2018), EVIYUD (Aliev et al, 2003b), GEJZAY (Mashevskaya et al, 2011), GIMGEQ (Sarkar et al, 2013), GITCAQ, GITDEV (Saha et al, 2017), IRUBUS (Aliev et al, 2003a), LIFBEJ, LIFBOT (Sun et al, 2011), NUXPIG (Wiedemann et al, 2009), PADHUA (Zonouz et al, 2015), PASTOT (Nicolaou et al, 2005), QIPNAH (Bhajammanavar et al, 2019), ROHNAG (Hosseinzadeh et al, 2019), TOMPER (Sakhno et al, 2008), UJEXOY (Ahankar et al, 2016), VILQEP (Gein et al, 2018), VIPNAJ (Mylari et al, 1991), VIQDOP (Guseinov et al, 2006), VOWGAP (Kazakov et al, 1990), WAPMIM (Dubovtsev et al, 2016), XINHIL (Aliev et al, 2001), XOKRAT, XOKRAT01 (Ramazani et al, 2019), YAJMOM (Wei et al, 2004), YIYFAP (Denislamova et al, 2014)]. All these structures and the title compound have the same electron density distribution within the 3-hydroxy-1,5-dihydropyrrol-2-one fragment.…”
Section: Database Surveymentioning
confidence: 99%
“…A search of the Cambridge Structural Database (CSD Version 5.42, update of November 2020; Groom et al, 2016) for the 3hydroxy-1,5-dihydro-pyrrol-2-one fragment revealed 79 hits. Only 27 of these hits contain a fragment with the same structure as that of the title compound [refcodes: BOQXEN (del Corte et al, 2019), CIKPAQ (Sarkar et al, 2018), EVIYUD (Aliev et al, 2003b), GEJZAY (Mashevskaya et al, 2011), GIMGEQ (Sarkar et al, 2013), GITCAQ, GITDEV (Saha et al, 2017), IRUBUS (Aliev et al, 2003a), LIFBEJ, LIFBOT (Sun et al, 2011), NUXPIG (Wiedemann et al, 2009), PADHUA (Zonouz et al, 2015), PASTOT (Nicolaou et al, 2005), QIPNAH (Bhajammanavar et al, 2019), ROHNAG (Hosseinzadeh et al, 2019), TOMPER (Sakhno et al, 2008), UJEXOY (Ahankar et al, 2016), VILQEP (Gein et al, 2018), VIPNAJ (Mylari et al, 1991), VIQDOP (Guseinov et al, 2006), VOWGAP (Kazakov et al, 1990), WAPMIM (Dubovtsev et al, 2016), XINHIL (Aliev et al, 2001), XOKRAT, XOKRAT01 (Ramazani et al, 2019), YAJMOM (Wei et al, 2004), YIYFAP (Denislamova et al, 2014)]. All these structures and the title compound have the same electron density distribution within the 3-hydroxy-1,5-dihydropyrrol-2-one fragment.…”
Section: Database Surveymentioning
confidence: 99%
“…Those from aldaric acids appear particularly attractive. The pathways via 2,5-dioxoadipic acid or 2,5-dihydroxymuconic acid as intermediates have been reported in the literature . They are, however, characterized by many reaction steps and low atom efficiency.…”
Section: Introductionmentioning
confidence: 99%